Determining real-time mass deposition with a quartz crystal microbalance in an electrostatic, parallel-flow, air-liquid interface exposure system. (January 2021) - Kaur, Kamaljeet; Overacker, Dana; Ghandehari, Hamidreza; Reilly, Christopher; Paine, Robert; Kelly, Kerry E.
Abstract: In vitro studies are the first step toward understanding the biological effects of particulate matter. As a more realistic exposure strategy than submerged culture approaches, air-liquid interface (ALI) in vitro exposure systems are gaining interest. One challenge with ALI systems is determining accurate particle mass deposition. Although a few commercially available ALI systems are equipped with online mass deposition monitoring, most studies use indirect methods to estimate mass doses. These different indirect methods may contribute to inconsistencies in the results from in vitro studies of aerosolized nanoparticles. This study explored the effectiveness of using a commercially available Quartz Crystal Microbalance (QCM) to estimate the real-time, particle-mass deposition inside an electrostatic, parallel-flow, ALI system. The QCM system required minor modifications, including custom-designed and fabricated headers. Three QCM systems were simultaneously placed in three of the six wells in the ALI exposure chamber to evaluate the uniformity of particle deposition. The measurements from fluorescein dosimetry and QCM revealed an uneven deposition between these six wells. The performance of the QCM system was also evaluated using two different methods. First, using fluorescein deposition in one well, depositions in three other wells were estimated, which was then compared to the actual QCM readings. Second, using the QCM measured deposition in one well, the deposition in three other wells was estimated and compared to deposition measured by fluorescein dosimetry. For both methods, the expected and actual deposition yields a linear fit with the slope 1. This good fit suggests that QCM systems can be used to measure real-time mass deposition in an electrostatic ALI system. Highlights: Commercial QCM systems can effectively measure mass deposition in an ALI system. Deposition in the six exposure wells of ALI is not uniform. Relative deposition parameters can address the well-to-well deposition differences. Deposition as low as 50 ng/cm 2 can be measured by QCM in electrostatic ALI system.